Atlas of neonatal electroencephalography - Mizrahi, Eli M.; Hrachovy, Richard A. (demosMEDICAL, 2016)
This comprehensive atlas presents the clinical practice of neonatal EEG through text, references, and detailed figures demonstrating normal and abnormal features of the neonatal EEG from the most premature infant to one month post-term. Each chapter contains dozens of full-page EEG images, along with detailed legends that place them in context, to emphasize specific components of the neonatal EEG as a benchmark for recognizing signature characteristics and interpreting clinical data. For the new Fourth Edition, Eli Mizrahi and Richard Hrachovy, established authorities in neonatal neurophysiology, have distilled the advances of the last ten years and provided the latest and best references for each chapter, updating their indispensable atlas to reflect current research and practice throughout.